An overview of critical energy infrastructure of the European Defence sector - Iliana Papamichael; Irene Voukkali; Kyriakos Vrionides; Pantelitsa Loizia; Marinos Stylianou; Paolo Sospiro; Marco Ciro Liscio; Vincenzo Naddeo; Antonis A. Zorpas (Energy Nexus, 2025)
The European Defence sector meets countless of challenges at the confluence of climate change and hybrid threats, which pose significant risks to critical energy infrastructure (CEI). This -paper aims to dissect these complex challenges and devise strategies to boost resilience within the European Defence sector though review process based on PRISMA statement using specific inclusion and exclusion criteria. By analyzing the interaction between climate-related risks, hybrid threat tactics, and vulnerabilities in energy security, this review paper seeks to shed light on effective policy frameworks, technological innovations, and capacity-building initiatives. In addition, paper aim to provide actionable insights that can enable policymakers, defence practitioners and stakeholders to navigate the evolving security landscape effectively. Ultimately, the manuscript strives to contribute to a deeper understanding of the intricate dynamics shaping energy security and defence in Europe, offering practical solutions to enhance resilience and mitigate the impact of emerging threats on CEI. It highlights climate change and hybrid threat impacts, offering insights for policymakers, stakeholders related with the defence sector, including Ministry of Defence as well as the entire energy sector. The paper seeks to prompt action for CEI, ensuring operational readiness and security in the European Defence sector as well as the results will be helpful for policy makers and relevant defence stakeholders to boost the sector to mitigate climate challenges